Parental autonomy vs. ability : attendance in a low-income elementary school - Holt, Charlotta (2018)
The overall aim of this study is to examine the perceptions of low-income elementary school parents with outstanding attendance concerns. This analysis makes salient the need for more complex treatment of the term parental agency in current U.S. educational scholarship by using a cross-disciplinary frame-work. Parental data subjects were collected within the context of a San Diegan NGO’s attendance initiative at a low-income elementary school in San Diego Unified School District. As an “Every Student Every Day” attendance intern, at-risk students with outstanding attendance concerns were added to my case-load at the start of the 2017-2018 school year. Ethnographic data in the form of case notes was collected and stored in the Social Work Client Management sys-tem known as 2-1-1 San Diego. Case notes comprised summaries of all out-reach, conversations, and engagements with students and families on the case load. Student attendance was tracked through PowerSchool and transcribed to Excel for the purposes of this study. Data in the form of focus groups was tran-scribed and collected on a monthly basis with interested parents who volun-teered to attend. The central contribution of the study is a renewed look at parental agency in low-income schools in the U.S. through the cross-disciplinary theoretical framework of the human capabilities approach. The research made evident that by treating agency with more nuance and care, a more productive examination of low-income families is made possible in current U.S. educational scholar-ship. Examining the data with this new theoretical framework encouraged a more genuine examination of family dynamics and parental decision-making.